Data security in internet of things based RFID and WSN systems applications - Sharma, Rohit; Mahapatra, Rajendra Prasad; Cengiz, Korhan (Boca Raton, FL : CRC Press, 2021)
"This book will focus on RFID (Radio Frequency Identification), IoT (Internet of Things), and WSN (Wireless Sensor Network). It will include contributions that discuss the security and privacy issues as well as the opportunities and applications that are tightly linked to sensitive infrastructures and strategic services. This book will address the complete functional framework and workflow in IoT-enabled RFID systems and explore the basic and high-level concepts. It is based on the latest technologies, and covers the major challenges, issues, and advances in the field. It will present data acquisition and case studies related to data intensive technologies in RFID-based IoT and includes WSN based systems and its security. It can serve as a manual for those in the industry while also helping beginners to understand both the basic and the advanced aspects in IoT-based RFID related issues. The book can be a premier interdisciplinary platform for researchers, practitioners, and educators to present and discuss the most recent innovations, trends, and concerns as well as practical challenges encountered and find solutions that have been adopted in the fields of IoT and analytics"--
OCLC-licensed vendor bibliographic record.
Keywords: Radio frequency identification systems -- Security measures; Wireless sensor networks -- Security measures; Internet of things -- Security measures; TECHNOLOGY / Manufacturing; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Engineering / Industrial